Capitalism and citizenship : the impossible partnership - Dean, Kathryn (London ; New York : Routledge, 2003)
This book investigates the potential for a new kind of citizenly sociability arising out of our societies of 'uncertainty' in which states and corporations are either denying the existence of uncertainty or attempting to transfer it to individuals (as in public and private pensions provisions).
Includes bibliographical references (p. [200]-221) and index.
osa 03/06/14
Loans
Keywords: Political participation; Capitalism